Menerapkan Prinsip 2 Timotius 1:7 dalam Pelayanan Penginjilan - Prabowo, Wisnu (MAGNUM OPUS: Jurnal Teologi dan Kepemimpinan Kristen, 2019)
As God's creation, humans are given spirits by God; the spirit has various functions and uses in life. In 2 Timothy 1: 7 it is written about the spirit of fear, a spirit that awakens strength, love and order. This article examines the meaning of "the spirit of fear, the spirit that awakens strength, love and order" in 2 Timothy 1: 7. This study is a qualitative study using descriptive methods of literature and text analysis. The results obtained are: First, God never gave a spirit that made the servants of God afraid in preaching the Gospel, but God gave a spirit that was able to have strength, love and self-control. So that, despite pressure and obstacles, God's servant is still able to carry out and finish his ministry in preaching the gospel. Abstract Sebagai ciptaan Allah, manusia diberikan roh oleh Allah; roh tersebut mempunyai berbagai fungsi dan juga kegunaan di dalam kehidupan. Di dalam 2 Timotius 1:7 tertulis tentang roh ketakutan, roh yang membangkitkan kekuatan, kasih dan ketertiban. Artikel ini mengkaji arti dari ungkapn â€œroh ketakutan, roh yang membangkitkan kekuatan, kasih dan ketertibanâ€ dalam 2 Timotius 1:7 tersebut. Kajian ini merupakan penelitian kualitatif yang menggunakan metode deskriptif literatur dan analisis teks. Hasil yang diperoleh adalah: Pertama, Tuhan tidak pernah memberikan roh yang menjadikan para pelayan Tuhan takut di dalam memberitakan Injil, namun Tuhan memberikan roh yang memampukan untuk mempunyai kekuatan, kasih dan penguasaan diri. Sehingga, walaupun mendapatkan tekanan dan hambatan, pelayan Tuhan tetap mampu melaksanakan dan menyelesaiakan pelayanannya dalam memberitakan Injil.